Efektifitas Pemberian Cincau Hijau (Premna oblongifolia Merr) dan Rebusan Daun Pandan Terhadap Perubahan Tekanan Darah Pada Penderita Hipertensi - Deayu Dwi Kania Fabialismaya; Ahmad Purnama Hudaya; Ria Inriyana (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
The most common non-communicable disease suffered by individuals in the world is hypertension. One of the provinces in West Java with the highest prevalence rate of hypertension is Sumedang Regency which is ranked 4th. Traditional plants such as green grass jelly and Pandan leaf can be used in herbal medicine to treat hypertension. The aim of this study was to compare blood pressure before and after being given green grass jelly (Premna oblongifolia Merr) and pandan leaf decoction for hypertension sufferers. Studyquasi experiment with a planpre test and post test nonequivalent control group design. The sample taken based on inclusion and exclusion criteria was 24 people. Sample selection uses techniquespurposive sampling. Data analysis techniques using statistical testspaired t test andindependent t test. Resultstestpaired t test shows a p value < 0,05 meansthere was a decrease after being given the intervention in both groups. Resultstestt-independent showing p value blood pressure systolic and diastolic > 0,05 meansThere is no significant difference between green grass jelly and boiled pandan leaves in reducing blood pressure in hypertension sufferers. The conclusion was that there was no difference in effectiveness between green grass jelly (Premna oblongifolia Merr) and pandan leaf decoction to reduce blood pressure in hypertension sufferers.